2020
DOI: 10.1007/s11252-020-01065-4
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking into the big city: influence of genetic and environmental factors on urban dragon lizard morphology and performance capacity

Abstract: Urban wildlife faces a novel set of challenges resulting in selective pressure that can lead to population-level changes. We studied Australian water dragons (Intellagama lesueurii) from urban and natural populations to test if urban populations differed in body size, shape, and performance capacity. If urban-derived morphology has arisen through selection, we predicted distinct morphological differences between wild dragons from urban and natural areas in both adult and hatchling life-stages. Urban hatchlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…and (2) What could be the functional significance of this morphological differentiation (i.e., fitness)? Here, we speculate that snout-vent length and jaw width may be adapted to local population densities given their relationship with agonistic behavior, conspecific density, and fitness (Husak et al 2006;Baxter-Gilbert et al 2020;Piza-Roca et al 2020). Additionally, these two traits may diverge between our city parks as dragons adapt to locally available food types or are constrained in their growth by the local resource availability.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…and (2) What could be the functional significance of this morphological differentiation (i.e., fitness)? Here, we speculate that snout-vent length and jaw width may be adapted to local population densities given their relationship with agonistic behavior, conspecific density, and fitness (Husak et al 2006;Baxter-Gilbert et al 2020;Piza-Roca et al 2020). Additionally, these two traits may diverge between our city parks as dragons adapt to locally available food types or are constrained in their growth by the local resource availability.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, as seen in the case of plasticityled evolution, phenotypic plasticity may precede and even facilitate adaptive changes to the genome (Irschick and Meyers 2007;Winchell et al 2016;Levis and Pfennig 2021). Indeed, previous work has shown that although there is a heritable component to morphology in eastern water dragons, trait expression may depend on environmental contexts (i.e., plasticity) (Baxter-Gilbert et al 2020). Furthermore, given this study was conducted on adult individuals, we are unable to account for genotype-environment interactions during development (Grishkevich and Yanai 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We used R version 3.5.0 to test for differences in morphological traits and bite force between males and females for each species (R Core Team 2018). All morphological traits and SVL were log 10transformed before analyses to ensure a scalar linear relationship (Lailvaux et al, 2004;Baxter-Gilbert et al 2020). First, we used a Type I analysis of variance (ANOVA) to test for a difference in SVL between sexes, which was performed using the R package 'car' and the function 'aov' (Fox & Weisberg 2019).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Much in the same way, island ecosystems have been seen to expedite phenotypic shifts and adaptation in insular populations (e.g., island mammal morphology [ 9 ]). So too have urban habitats driven rapid phenotypic change in a variety of traits (i.e., urban evolution [ 7 ]), such as behavior [ 10 , 11 , 12 ], morphology [ 13 , 14 , 15 ], and performance capacity [ 16 ]. Many of the challenges and selective forces faced by colonizing populations—whether they be in novel island ecosystems or urban landscapes—can be quite similar, such as novel resources [ 17 , 18 , 19 ], sources of mortality [ 20 , 21 ], and altered thermal or hydric conditions [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%